Effect of lncRNA MALAT1 on the Granulosa Cell Proliferation and Pregnancy Outcome in Patients With PCOS - Tu, Mixue; Wu, Yiqing; Wang, Feixia; Huang, Yun; Qian, Yuli; Li, Jingyi; Lv, Pingping; Ying, Yanyun; Liu, Juan; Liu, Yifeng; Zhang, Runju; Zhao, Wei; et al. (Frontiers in Endocrinology, 2022)
Follicle arrest is one of the main characteristics of polycystic ovary syndrome (PCOS), the most common endocrinological disorder in reproductive aged women. Increasing evidences prove that high anti-Mullerian hormone (AMH) levels may play an important role in follicular development. Long non-coding RNA (lncRNA) with a length of more than 200nt is widely involved in the directional differentiation, growth and development of cells. Whereas whether lncRNA is involved in AMH’s role in follicular development is unknown. In this study, we analyzed lncRNA expression in ovarian granulosa cells (GCs) collected from women with and without PCOS via high-throughput sequencing. The results showed that a total of 79 non-coding transcripts were differently expressed in GCs of PCOS patients, including up-regulated lncRNA MALAT1. The up-regulation of MALAT1 was further confirmed by RT-qPCR in GCs from a larger cohort of PCOS patients. Further, knockdown MALAT1 can promote the proliferation of KGN cell in vitro. These data suggested a role for MALAT1 in the development of PCOS. Meanwhile, MALAT1 and phosphorylated SMAD 1/5  (Ser463/465) protein were up-regulated in KGN cells after exogenous AMH stimulating, which identified AMH perhaps as an regulator for the expression of MALAT1. Also, we found that MALAT1 can predict clinical pregnancy outcome to a certain extent by ROC curve analysis (area:0.771, P=0.007, 95% CI:0.617-0.925, sensitivity:57.1%, specificity:91.7%). Thus, our findings revealed a role of lncRNA MALAT1 in inhibiting granulosa cells proliferation and may be correlated with pregnancy outcome in PCOS.